ANALISIS LITERASI SAINS PESERTA DIDIK SMA PADA MATERI FLUIDA DINAMIS - Fitriatus Sabrina; Fida Rachmadiarti; Titin Sunarti (JPPS (Jurnal Penelitian Pendidikan Sains), 2021)
The research aims to analyze the scientific literacy of senior high school students on fluid dynamics. Research was implemented at SMA Negeri 3 Nganjuk. The population in this research were senior high school students. The sampling technique in this research was random cluster sampling. The sample in this research amounted to 36 students. Three instruments are used in the data collection technique, interviews, scientific literacy tests, and questionnaires. The data analysis used in this research is the percentage of students' scientific literacy achievement in the competency domain. This research shows that students' literacy ability is relatively low. The percentages obtained for each competency are the competence to explain scientific phenomena by 44% in the low category, evaluate and design scientific investigations by 47% in the low category, and interpret scientific data and evidence by 56% in the low category. This research concludes that the scientific literacy of senior high school students on fluid dynamics is in a low category. One of the causes is that the student's ability is only memorizing and not relating various science topics or applying complex concepts to solve problems in their everyday lives. The research implications can provide information related to scientific literacy skills in senior high school students on fluid dynamics according to the competencies that have been presented.